2020
DOI: 10.2147/ijn.s229858
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-Assembled Nanoparticles Prepared from Low-Molecular-Weight PEI and Low-Generation PAMAM for EGFRvIII-Chimeric Antigen Receptor Gene Loading and T-Cell Transient Modification</p>

Abstract: Background: The complex preparation procedures and severe toxicities are two major obstacles facing the wide use of chimeric antigen receptor-modified T (CAR-T) cells in clinical cancer immunotherapy. The nanotechnology-based T cell temporary CAR modification may be a potential approach to solve these problems and make the CART cell-based tumor therapy feasible and broadly applicable. Methods: A series of plasmid DNA-loaded self-assembled nanoparticles (pDNA@SNPs x/y) prepared from adamantane-grafted polyamido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…have demonstrated that self-assembled nanoparticles (SNPs) prepared from cyclodextrin-grafted low molecular weight PEI (CD-PEI800) presented low cytotoxicity and a high transfection efficiency to Jurkat cells. They postulated that the cationic hydrogel generated from CD-PEI800 contributed to SNPs’ enhanced gene encapsulation efficiency ( 64 ).…”
Section: Hybrid Vector Systems For Transfection Enhancement and Cytotoxicity Reductionmentioning
confidence: 99%
“…have demonstrated that self-assembled nanoparticles (SNPs) prepared from cyclodextrin-grafted low molecular weight PEI (CD-PEI800) presented low cytotoxicity and a high transfection efficiency to Jurkat cells. They postulated that the cationic hydrogel generated from CD-PEI800 contributed to SNPs’ enhanced gene encapsulation efficiency ( 64 ).…”
Section: Hybrid Vector Systems For Transfection Enhancement and Cytotoxicity Reductionmentioning
confidence: 99%
“…The complex successfully delivered the plasmid with EGFRvIII-CAR to Jurkat T cells, which specifically recognized EGFRvIII-positive cancer cells ( Figure 7 ). This study has demonstrated the high transient CAR transfection efficiency and low toxicity towards Jurkat T cells, which, in the view of the research team, can be used in future in vivo and ex vivo studies of the given complex, forming a basis for potential clinical trials [ 153 ].…”
Section: Recent Advancements In Cancer Gene Therapy Studies Using mentioning
confidence: 99%
“…Abbreviations: pDNA, plasmid DNA; Ad-PEG, adamantane-grafted poly(ethylene glycol); Ad-PAMAMx, adamantane-grafted polyamidoamine dendrimer (x: PAMAM dendrimer generation); CD-PEIy, cyclodextrin-grafted branched polyethylenimine (y: PEI molecular weight); SNPs, self-assembled nanoparticles; EGFRvIII, epidermal growth factor receptor variant III; CAR, chimeric antigen receptor; pEGFRvIII-CAR, epidermal growth factor receptor variant III-chimeric antigen receptor expression plasmid. With the permission of [ 153 ], copyright (2021) Dove Medical Press.…”
Section: Figurementioning
confidence: 99%
“…The results of the study showed the ability of LNPs to deliver mRNA from the CAR to primary T cells and generate functional CAR T cells that have the potential to induce cancer cell death [ 159 ]. Furthermore, another approach to reprogramming T cells is to use nanocarriers to deliver drugs, antibodies, and interleukins, as they can protect T cells from immunosuppression and activate CD8+ T cells [ 160 , 161 , 162 , 163 , 164 ].…”
Section: 3 T Cellsmentioning
confidence: 99%